Mass Casualty Incidents - Lynn, Mauricio (Springer New York : Imprint: Springer, 2016)
This manual is aimed to provide health care professionals, at the scene and at hospitals, as well as allied organizations, a practical and operational approach for planning the response to mass casualty incidents (MCI's), with emphasis to the types of events that are sudden in nature, resulting in a number of injured or contaminated patients that overwhelm the local health care system. From activation of the MCI plan to the specific medical care of multiple simultaneous patients, the manual offers checklists and algorithms of "what to do" during the first minutes after a MCI occurred. The manual is designed to be adapted and modified for specific institutions according to their size and capabilities. Written by a world expert in the field of MCI management, Mass Casualty Incidents: The Nuts and Bolts of Preparedness and Response for Acute Disasters is a valuable resource for all health care professionals and institutions that deal with mass casualty incidents. .